Impact of Urban Landscaping on Improving the Sustainable Development of the Urban Environment. The Case of Nur-Sultan - OSPANGALIYEV, Askhat; UTEBEKOVA, Ainur; DOSMANBETOV, Daniyar; AKHMETOV, Ruslan; MAZARZHANOVA, Kuralay (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).21, 2022)
For modern metropolitan cities, one of the important problems that need to be solved is minimizing the risks of critical environmental issues in the conditions of climate change and degradation of natural resources. Environmental problems of cities lead to a decrease in their natural potential and are now coming to the fore. The concept of the modern development of the metropolitan city necessarily includes measures to comprehensively address issues of urban landscaping, preservation of cultural and historical heritage, and the formation of a sustainable environment. In this paper, considering compliance with environmental, social, and governance principles and based on an expert survey, an analysis of the case "Management of landscaping of the city of Nur-Sultan" and statistical data of the Department of Environmental Protection and Nature Management of Nur-Sultan, the main problems of landscaping in Nur-Sultan (Kazakhstan) have been identified and the situation of green spaces has been analyzed, together with the possibilities of planning a system of urban landscaping. With the help of GIS technology, an assessment of green spaces has been made. Materials from space images of the Sentinel-2 satellite have been loaded into the GIS. It has been concluded that urban landscaping in Kazakhstan continues to be based on recreational standards, whereas ecosystem planning of sustainable cities is a recognized European strategic approach, and the leading trend is the transition from uncontrolled territorial sprawl to structural reorganization of urban areas.